Comparison of Life Skills between Intercollegiate Athletes and Non-Athletes of Government Girls Higher Secondary Schools of District Mardan, Pakistan - Abdul Waheed Mughal; Asia Noor; Tasleem Arif (The Sky, 2023)
This study aimed to compare the life skills about interpersonal relationship skills, stress management skills, and decision-making skills amongst intercollegiate athletes and non-athletes of government girls’ higher secondary schools in district Mardan, Pakistan. The researcher followed a descriptive survey research design to meet the set objectives of the study. girl athletes and non-athletes from Government Higher Secondary schools of District, Mardan with age range 15-21 years of class 9th, 10th, 1st year, and 2nd year constituted the target population for the current study. A close-ended adapted questionnaire University of Pretoria (South Africa) using a Likert scale from “strongly disagree” to “strongly agree” was used to collect the required information from the participants consisting of girls’ athletes and non-athletes from government higher secondary schools of district, Mardan. A total of 568 questionnaires were administered among the participants and 468 questionnaires with (an 82.39%) ratios were received back. For an inclusive assessment of life skills, different attributes were labeled to each life skill, whereas all 34 items were assigned to 04 skills in the questionnaire. The collected data were properly tabulated and processed through descriptive and inferential statistical techniques. The findings of the study indicated that sport has produced a positive role in the development of life skills among athletes as compared with non-athletes. This finding can be helpful for those who intend to develop and promote the sport in their respective areas. It has been concluded that participants acknowledged the role that sport has essential in the development of life skills such as interpersonal relationships (2.90), stress management (2.37), decision making (2.66), and problem-solving skills (2.49). However, it was noticed that urban school athletes produced a higher mean score on one life skill such as interpersonal relationships (2.93) and the rest of life skills mean scores are lower. It is recommended that school sports participation of girls may be ensured/enhanced to develop and promote the positive life skills necessary for products as well as a dynamic role in society.